Pemanfaat Energi Matahari Untuk Pompa Air Dan Penerangan Dalam Program Pengabdian Kepada Masyarakat - Fri Murdiya; Amir Hamzah; Azriyenni Azhari Zakri; Nurhalim Nurhalim; Firdaus Sutan; Suwitno Suwitno (LPPM UMRI, 2020)
Community service program is a mandatory activity for higher eduacation in community empowerment and development. These activities include training programs and application of appropriate technology including the utilization of solar energy for water pumps in orphanages in Rokan Hulu regency and the street lighting program in Simpang Petai village, Kampar regency in Riau province. This activity also considers to the obstacles faced by the community with offering and implementing appropriate technology to them as beneficiaries. This activity takes place with the involvement of students in work and lecture program (KKN) that integrated with community service activities.It is shown that the community as beneficiaries have joined diligently and received assistance with this program by implementation of solar water pump and street lighting. The evaluation of this activity shows that collaboration continues between the community and the Department of Electrical Engineering, Faculty of Engineering, University of Riau and the communitis feel helped and there is an improvement in the electricity infrastructure in their village. This activity was carried out in a fostered village by the Faculty of Engineering, University of Riau.